2000
DOI: 10.1097/00000658-200005000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minimally Invasive Radioguided Parathyroidectomy on Efficacy, Length of Stay, and Costs in the Management of Primary Hyperparathyroidism

Abstract: ObjectiveTo compare the first 20 patients who underwent minimally invasive radioguided parathyroidectomies (MIRPs) performed at the authors' institution with 20 similar patients who underwent a more conventional surgical approach for primary hyperparathyroidism. Summary Background DataThe technique of parathyroidectomy has traditionally involved a bilateral exploration of the neck with the intent of visualizing four parathyroid glands and resecting enlarged parathyroid glands. Parathyroid scanning using radioi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
115
0
12

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(129 citation statements)
references
References 22 publications
2
115
0
12
Order By: Relevance
“…Recientemente también se han empleado otros nuevos abordajes o métodos para la cirugía míni-mamente invasiva, como son la cirugía radioguiada con gammacámara intraoperatoria 12 o la paratiroidectomía endoscópica. Esta última la realizan dos grupos europeos.…”
Section: Discussionunclassified
“…Recientemente también se han empleado otros nuevos abordajes o métodos para la cirugía míni-mamente invasiva, como son la cirugía radioguiada con gammacámara intraoperatoria 12 o la paratiroidectomía endoscópica. Esta última la realizan dos grupos europeos.…”
Section: Discussionunclassified
“…MIP has advantages over bilateral 4-gland exploration including decreased operative time, lower hospital costs, shorter lengths of stay, and fewer episodes of postoperative hypocalcemia (18)(19)(20)(21)(22)(23). Another potential benefit of MIP is the unilateral neck exploration that leaves the contralateral side relatively free of scarring and makes future neck operations less difficult.…”
Section: Parathyroidectomymentioning
confidence: 99%
“…Many studies have shown that minimally invasive parathyroidectomy offers advantages like reduced hospital costs, shorter hospital stays, a lower incidence of hypocalcemia, and equally high cure rates with lower complication rates (Udelsman R, 2002;Goldstein et al, 2000).…”
Section: Parathyroidectomy: "The Dawn Of a New Concept"mentioning
confidence: 99%